(untitled) (Journal of Dhaka Medical College, 2015)
Context: Osteoarthritis (OA) is the most common form of arthritis accounting for about 30% of general physician visits. Intrarticular (IA) corticosteroid injections have been used for decades in clinical practice for pain relief and control of local inflammation in OA. In the present study a combined therapy of long acting intra-articular injection in addition to physical modalities of OA knee was given to find out the functional improvement and clinical outcome of the patient. Methods: It was a prospective interventional non-randomized clinical study conducted in the Department of Physical Medicine & Rehabilitation, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from October, 2011 to March, 2012. Fifty four patients between 35 and 75 years without consideration of gender with a history of not less than three months knee pain with radiographic confirmation of primary osteoarthritis were selected purposefully. Then they were divided randomly in group A and B, having 27 patients in each group. Group A received NSAID (non steroidal anti-inflammatory drugs) i.e. aceclofenac 100mg twice daily for 10 days + omeprazol 20mg twice daily for 10 days + MWD (micro wave diathermy 20 minutes for 14 days. + therapeutic exercise + ADL (activities of daily living), while Group B received 80mg intraarticular triamcinolon acetonide injection once followed by NSAID i.e. aceclofenac 100mg twice daily for 10 days + omeprazol 20mg twice daily for 10 days + MWD 20 minutes for 14 days. + therapeutic exercise + ADL. In both groups the patients were observed for six weeks. Results: The mean of age of patients in group A and B were 52.33±9.62 years and 52.29±9.67 years respectively. In group A, 9 (33.3%) were male and 18 (66.7%) were female. In group B, 10 (37.0%) were male and 18 (63.0%) were female. Mean visual analogue scale (VAS) during pre treatment in group A and group B were 6.22±1.60 and 7.15±1.56 respectively. Mean range of motion (ROM) during pre treatment in group A and group B were 117.33±13.05 and 112.37±19.01 respectively. Mean time taken to walk 50 feet during pre treatment in group A and group B were 18.22±2.39 and 18.81±2.13 minutes respectively. Mean Western Ontario and Mc Master Universities (WOMAC) index in group A and group B were 60.85±15.86 and 67.33±16.33 minutes respectively. After treatment in both groups visual analogue scale (VAS), range of motion (ROM), time taken to walk 50 feet and Western Ontario and Mc Master Universities (WOMAC) index gradually decreased and range of motion (ROM) gradually increased, which were statistically significant. However, the study conducted with small sample size in a single centre in Dhaka city, which may not be representative for the whole country. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22694 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 48-54